2011
DOI: 10.1177/1479164111408938
|View full text |Cite
|
Sign up to set email alerts
|

Circulating endothelial progenitor cells in women with gestational alterations of glucose tolerance

Abstract: Endothelial progenitor cells (EPCs) play a role in angiogenesis during pregnancy. The aim of this study was to evaluate circulating EPCs in pregnant women with gestational alterations of glucose tolerance. Glucose tolerance, insulin sensitivity and β-cell function were derived from oral glucose tolerance tests in 23 women with normal glucose tolerance (NGT), 18 with gestational impaired glucose tolerance (GIGT) and 24 with gestational diabetes mellitus (GDM). Circulating cells expressing CD34 in combination wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…In contrary to normal pregnancy, a significantly lower number has been found in pregnant patients with gestational diabetes mellitus and preeclampsia. 26 There are no previous studies looking at circulating EPCs in patients with PPCM.…”
Section: Angiogenic Imbalance In Post-ppcm Women With LV Recoverymentioning
confidence: 99%
“…In contrary to normal pregnancy, a significantly lower number has been found in pregnant patients with gestational diabetes mellitus and preeclampsia. 26 There are no previous studies looking at circulating EPCs in patients with PPCM.…”
Section: Angiogenic Imbalance In Post-ppcm Women With LV Recoverymentioning
confidence: 99%
“…Indeed, in previous studies, the recruitment of EPCs was suppressed in both prediabetic patients [13] and women in gestational alterations of glucose tolerance [14], EPCs' declining number correlated with diminished vascular repair capability in both prediabetic [15] and diabetic patients [16]. However, so far, no study has been reported relating to the underlying mechanism of why the inability of circulating EPCs is present in prediabetic individuals.…”
Section: Introductionmentioning
confidence: 95%
“…Recent studies reported that GDM affects the growth and functions of endogenous stem or progenitor cells by inducing oxidative stress, senescence and mitochondrial dysfunctions. For examples, women with GDM have reduced concentration of circulating endothelial progenitor cells in late stages of pregnancy when compared with women without GDM (Acosta et al, 2011; Buemi et al, 2007; Penno et al, 2011). Two recent studies have demonstrated the adverse effect of GDM on proliferation, viability, differentiation and mitochondrial functions in mesenchymal stem cells (MSCs) derived from human umbilical cord (UC) (Kim et al, 2015; Wajid et al, 2015).…”
Section: Introductionmentioning
confidence: 99%